Designing a general anti-abuse rule: striking a balance - Freedman, J (International Bureau of Fiscal Documentation, 2014)
This article argues that statutory general anti-avoidance or anti-abuse provisions (GAARs) are an essential part of a modern tax system, since specific legislation will not catch every abuse. Properly drafted GAARs with appropriate protections can give administrators and courts an important tool to use in cases of egregious abuse, but the use must be within a legitimate framework suitable for the jurisdiction in question. GAARs are not the appropriate mechanism for a fundamental rewriting of domestic or international tax law, but they are a valuable element of the statute book in the fight to combat artificial tax arrangements.